1987
DOI: 10.1172/jci112791
|View full text |Cite
|
Sign up to set email alerts
|

Extended major histocompatibility complex haplotypes in patients with gluten-sensitive enteropathy.

Abstract: We have studied major histocompatibility complex markers in randomly ascertained Caucasian patients with gluten-sensitive enteropathy and their families. The frequencies of extended haplotypes, defined as haplotypes of specific HLA-B, DR, BF, C2, C4A, and C4B allelic combinations, occurring more frequently than expected, were compared on patient chromosomes, on normal chromosomes from the study families, and on chromosomes from normal families. Over half of patient chromosomes consisted almost entirely of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…Thus, the strong linkage disequilibrium normally observed between the HLA-DR and -DQ subregions would be extended, on this haplotype, throughout the entire HLA-D region. The celiac disease-associated HLA-DR3 haplotype was recently shown to be extended telomerically from the subregion encoding HLA-DR3 through the genes encoding the complotype SC01 to the HLA-B8 locus (26). Similarly, our findings indicate that this HLA-DR3, -DQw2 haplotype may have an unusual degree of linkage disequilibrium, extending centromerically from the HLA-DR subregion to the HLA-DP subregion.…”
Section: Methodssupporting
confidence: 71%
“…Thus, the strong linkage disequilibrium normally observed between the HLA-DR and -DQ subregions would be extended, on this haplotype, throughout the entire HLA-D region. The celiac disease-associated HLA-DR3 haplotype was recently shown to be extended telomerically from the subregion encoding HLA-DR3 through the genes encoding the complotype SC01 to the HLA-B8 locus (26). Similarly, our findings indicate that this HLA-DR3, -DQw2 haplotype may have an unusual degree of linkage disequilibrium, extending centromerically from the HLA-DR subregion to the HLA-DP subregion.…”
Section: Methodssupporting
confidence: 71%
“…Destacam-se, entre esses, os achados de Alper, et al (57) , demonstrando aumento na freqüência dos haplótipos [HLA-B8, DR3, BF*S, C2*C, C4A*Q0, C4B*1] e [HLA-B44, DR7, BF*F, C2*C, C4A*3, C4B*1] em pacientes celíacos caucasóides, bem como os resultados obtidos por Mannion, et al (58) com aumento do haplótipo [HLA-B8, DR3, DQW2, BF*S, C4A*Q0 e C4B*1] em pacientes irlandeses. Estudos com pacientes italianos caracterizaram aumento significativo na freqüência do alelo BF*F1, em relação a população normal, e uma associação de BF*F1 com Dw3 e de BF*F com Dw7 (59) .…”
Section: O Complemento Na Patogenia Das Doençasunclassified
“…In North European populations, the DQA1*05 and DQB1*02 alleles are frequently present on the extended HLA-B8-DR3-DQ2 haplotype. 6,9 This haplotype has also been shown to be associated with other autoimmune disorders, including type I diabetes mellitus, systemic lupus erythematosus, Graves' disease, Hashimoto's disease and myasthenia gravis, suggesting that the genes on this haplotype are involved in autoimmunity in general (for a review, see Candore et al 10 ). In coeliac disease, it was shown that different DQ2 genotypes account for different disease risks.…”
Section: Introductionmentioning
confidence: 99%